2013
DOI: 10.1007/s12263-013-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

The fermented non-digestible fraction of common bean (Phaseolus vulgaris L.) triggers cell cycle arrest and apoptosis in human colon adenocarcinoma cells

Abstract: Cancer is a leading cause of death worldwide with colorectal cancer (CRC) ranking as the third contributing to overall cancer mortality. Non-digestible compounds such as dietary fiber have been inversely associated with CRC in epidemiological in vivo and in vitro studies. In order to investigate the effect of fermentation products from a whole non-digestible fraction of common bean versus the short-chain fatty acid (SCFAs) on colon cancer cells, we evaluated the human gut microbiota fermented non-digestible fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…In their study, the fermentation product was found to selectively inhibit cancer cell proliferation and induced cell death . In addition, fermented common bean ( Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells . More specifically, our results have demonstrated that FMB possessed greater apoptosis inducing effect against breast cancer cells than FSB.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In their study, the fermentation product was found to selectively inhibit cancer cell proliferation and induced cell death . In addition, fermented common bean ( Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells . More specifically, our results have demonstrated that FMB possessed greater apoptosis inducing effect against breast cancer cells than FSB.…”
Section: Discussionsupporting
confidence: 51%
“…45 In addition, fermented common bean (Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells. 46 More specifically, our results have demonstrated that FMB possessed greater apoptosis inducing wileyonlinelibrary.com/jsfa effect against breast cancer cells than FSB. The disparities of the cytotoxic efficacy between studies might be contributed by the conditions of fermentation as well as the extraction process prior to the in vitro studies.…”
Section: Discussionmentioning
confidence: 59%
“…However in Northern Mexico, Bayo Victoria beans have had traditionally higher preference from consumers, and therefore they are also used by the food industry for processing and marketing. In previous reports, we have indicated that Bayo Victoria beans have antioxidant and anti‐inflammatory activities (Moreno‐Jiménez et al, ), containing phenolic compounds with antiproliferative effects as described also in the literature (Campos‐Vega et al, ; Cruz Bravo et al, ; ). These studies indicate that Phaseolus vulgaris consumption can be recommended for cancer prevention.…”
Section: Introductionsupporting
confidence: 56%
“…Vergara-Castañeda et al (2010) have determined the chemoprotective effect at early stages of colon cancer (in vivo models). In this context, multiple mechanisms have been suggested, when evaluating common bean effects in cell survival (Cruz-Bravo et al, 2011), cell cycle arrest and apoptosis in human colon adenocarcinoma cells (Cruz-Bravo et al, 2014).…”
mentioning
confidence: 99%
“…Propionate participates in the succinate pathway and acrylate pathway [39]. And propionate as well as butyrate can induce apoptosis of human colon carcinoma cells which are infinite proliferous and finally lead to tumours [40]. This discovery may provide a clue to help clean those carcinoma cells in a 'healthy' way.…”
Section: Functional Metabolites Produced By the Gut Microbiotamentioning
confidence: 94%